A composite material containing activated carbon and its preparation method and application

By synchronously introducing nanometal oxide particles in situ into the activated carbon pore channels, the activated carbon-containing composite materials are prepared, which solves the uniformity and stability problems caused by the independent preparation process of carbon materials and metal oxide composite materials in the prior art, and achieves high specific capacitance and good cycling stability.

CN116072442BActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202111276727.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-30
Publication Date
2025-05-02
Estimated Expiration
2041-10-30

AI Technical Summary

Technical Problem

In the preparation process of existing carbon materials and metal oxide composite materials, the preparation of carbon materials and metal oxides is an independent process, resulting in poor uniformity of the composite materials and many structural defects, which affects the long-term stability of the electrode.

Method used

By synchronously introducing nanometal oxide particles in situ during the formation of activated carbon pore structure, binary composite precipitation method is used to prepare chemical precipitation method or redox precipitation method, and mixed with petroleum coke raw materials and activator. After activation and oxidation treatment, activated carbon-containing composite materials are prepared.

Benefits of technology

The uniform dispersion of metal oxides on the inner and outer surfaces of activated carbon is achieved, the electrochemical performance and long-term stability of the composite material are improved, and the high specific capacitance, good rate performance and good cycle stability are achieved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a composite material containing activated carbon and a preparation method and application thereof. The preparation method comprises the following steps: (1) preparing a binary composite precursor containing a first metal and a second metal; (2) mixing the binary composite precursor, a petroleum coke raw material, and an activator to obtain a composite material precursor; (3) performing an activation treatment on the composite material precursor; (4) performing an oxidation treatment on the activated product, and then washing and drying to obtain an activated carbon-containing composite material. The activated carbon-containing composite material comprises a first metal oxide, a second metal oxide, and activated carbon. A working electrode comprising the composite material is also provided. In the preparation method of the composite material containing activated carbon of the present invention, the composite process of the metal oxide and the carbon material is carried out simultaneously with the activation process of the petroleum coke, thereby achieving uniform dispersion of the metal oxide on the inner and outer surfaces of the activated carbon, achieving structural stability of the active components of the composite material, and thereby increasing its long-term stability during electrochemical testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to an activated carbon composite material for supercapacitors and a preparation method thereof. Background Art

[0002] With the development of science and technology, the development of high-performance and environmentally friendly new energy storage devices has become a current research hotspot. Supercapacitors are energy storage devices with performance between traditional capacitors and batteries. With excellent cycle stability and highly reversible fast charge and discharge performance, they have great application potential in new energy vehicles, wind energy, aerospace, electronic communications and other fields.

[0003] Supercapacitors are mainly composed of four parts: electrolyte, electrode material, current collector and diaphragm. The electrode material is one of the most critical factors affecting supercapacitors. According to the energy storage mechanism of the electrode material, supercapacitors can be divided into double-layer capacitors and Faraday pseudocapacitors (pseudocapacitors). Carbon materials such as activated carbon, carbon nanotubes, graphene, activated carbon fibers, etc. are representative electrode materials for double-layer capacitors. At the same time, metal oxides represented by NiO, Co3O4, and MnO2 are representative pseudocapacitor electrode materials.

[0004] Pseudocapacitive electrode materials have high capacitance values. Under the condition of the same specific surface area, the specific capacitance value is about 10 to 100 times that of double-layer electrode materials. The redox reaction of ruthenium oxide on the surface in aqueous electrolyte is highly reversible, and the specific capacitance value is much higher than that of carbon materials and conductive polymers, but it is expensive. MnO2 is low-cost, has low pollution, and a wide voltage window. The theoretical specific capacitance value reaches 1380 F / g. When used as an electrode material, metal oxides often have poor conductivity and high resistivity, resulting in large capacitance loss at high current density. Problems such as volume expansion effect and active material particle rupture seriously affect the long-term stability of the electrode.

[0005] Activated carbon is the earliest carbon electrode material used in supercapacitors and is also the most studied electrode material at present. As a supercapacitor electrode material, the attraction of activated carbon lies in its good conductivity, ultra-high specific surface area of ​​more than , and adjustable pore structure. In addition, activated carbon also has the advantages of abundant raw materials, low price, good processing performance, and stable chemical properties. Activated carbon has become the electrode material for supercapacitors with the most industrial prospects.

[0006] When the same type of electrode material is used alone, there will always be certain performance limitations, and it cannot fully meet the performance requirements of supercapacitors in all aspects. When carbon materials are combined with metal oxides and used as electrode materials, not only can the metal oxides ensure the specific capacitance of the composite material, but also the skeleton support of the carbon material can well alleviate the possible structural collapse of the metal oxide during the charge and discharge process, ensuring the transfer of electrons.

[0007] At present, the preparation process of composite materials of carbon materials and manganese dioxide mostly selects relatively expensive carbon nanotubes and graphene as carbon precursors. Patent CN 108217733 A uses graphite as raw material, intercalates and expands graphite through intercalation agents, oxidants, and expanders to obtain graphene-like expanded graphite, and then reacts with potassium permanganate to grow manganese dioxide on carbon nanosheets to obtain carbon-manganese dioxide composite materials. Patent CN 109637839 A discloses a carbon nanotube / manganese dioxide composite electrode material, which uses carbon cloth treated with nitric acid to load carbon nanotubes, and then uses potassium permanganate and manganese sulfate as manganese sources for hydrothermal synthesis to prepare composite electrode materials. Patent CN 105826088 B uses potassium permanganate as a precursor to in-situ redox-grow manganese dioxide nanosheets on the surface of a carbon aerogel with a three-dimensional network structure composed of one-dimensional carbon nanofibers and two-dimensional flaky carbon to obtain a carbon aerogel / manganese dioxide composite electrode material. The high specific surface area and porosity of the carbon aerogel improve the defects of poor conductivity and small specific surface area of ​​manganese dioxide, so that the composite material has more chemical reaction sites and electrolyte conduction paths, and the electrochemical performance is greatly improved. However, the preparation process of carbon aerogel using polyacrylonitrile as raw material is very complicated. Patent CN 105405680 A uses manganese sulfate and potassium permanganate as manganese sources to prepare manganese dioxide nanosheets through hydrothermal synthesis, and then uses methane as a carbon source and adopts chemical vapor deposition to prepare carbon particles / manganese dioxide composite electrode materials through carburization treatment to solve the problems of high internal resistance and poor charge and discharge stability of manganese dioxide. Summary of the invention

[0008] Based on the problems existing in the prior art, the present invention aims to provide a composite material containing activated carbon and its preparation method and application, the preparation of metal oxide and the preparation process of activated carbon are carried out simultaneously, nano metal oxide particles are introduced in situ in the process of continuous formation of the activated carbon pore structure, the fusion of the two materials is realized at the molecular level, the advantages of the two materials are synergistically exerted, and the prepared composite material has the advantages of high specific capacitance, good rate performance and good cycle stability when used as a supercapacitor electrode material. The problem that the current carbon material / metal oxide composite material preparation technology mostly uses graphene, carbon nanotubes, carbon aerogel and other carbon precursors with good conductivity is solved, and the performance of the composite material is improved by improving the preparation method and structural properties of the carbon precursor, but the preparation of carbon material and metal oxide are two independent processes. Whether it is synthesizing carbon material first and then synthesizing metal oxide by hydrothermal method or synthesizing metal oxide of a certain crystal form and then carburizing, the prepared composite material has relatively poor uniformity and many structural defects.

[0009] In order to achieve the above-mentioned object of the invention, the first aspect of the present invention provides a method for preparing a composite material containing activated carbon, comprising the following steps:

[0010] (1) preparing a binary composite precursor containing a first metal and a second metal;

[0011] (2) mixing the binary composite precursor obtained in step (1), a petroleum coke raw material, and an activator to obtain a composite material precursor;

[0012] (3) activating the composite material precursor under inert atmosphere conditions to obtain an activated product;

[0013] (4) The activated product is oxidized under oxidative atmosphere conditions, and then further washed and dried to obtain an activated carbon-containing composite material.

[0014] Furthermore, in the above-mentioned preparation method of the activated carbon-containing composite material, the first metal is selected from one or more of the metals of Group VIIB and Group VIII, and specifically can be one or more of manganese, nickel, and cobalt, preferably manganese.

[0015] Furthermore, in the above method for preparing the activated carbon-containing composite material, the second metal is at least one of the rare earth elements, preferably lanthanum and / or cerium.

[0016] Furthermore, in the above-mentioned method for preparing the composite material containing activated carbon, the binary composite precursor containing the first metal and the second metal in step (1) can be prepared by chemical precipitation method or redox precipitation method. The specific preparation process is as follows:

[0017] (I) The specific preparation process of the chemical precipitation method is as follows: the first metal precursor and the second metal precursor are mixed with water, the pH value of the system is adjusted to 7.0-10.0, and then the binary composite precursor is obtained through aging, separation, water washing and drying.

[0018] Furthermore, in the specific preparation process of the above chemical precipitation method, the first metal precursor is a salt containing the first metal, which can be an inorganic salt and / or an organic salt, specifically one or more of nitrate, sulfate, acetate, and chloride. Furthermore, the first metal precursor is one or more of manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, nickel nitrate, nickel chloride, nickel acetate, nickel sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, and cobalt sulfate.

[0019] Furthermore, in the specific preparation process of the above-mentioned chemical precipitation method, the second metal precursor is a rare earth element compound, preferably a cerium or lanthanum compound, and can be specifically selected from one or more of cerium nitrate, cerium sulfate, cerium chloride, cerium acetate, lanthanum chloride, lanthanum nitrate, lanthanum sulfate, and lanthanum acetate.

[0020] Furthermore, in the specific preparation process of the above chemical precipitation method, the weight ratio of the first metal precursor to the second metal precursor is 10:1 to 1:1, preferably 8:1 to 2:1.

[0021] Furthermore, in the specific preparation process of the above chemical precipitation method, the total molar concentration of the first metal precursor and the second metal precursor in the aqueous solution is 0.05 to 2.0 mol / L, preferably 0.05 to 1.5 mol / L.

[0022] Furthermore, in the specific preparation process of the chemical precipitation method, the mixing temperature of the first metal precursor, the second metal precursor and water is 20 to 80° C., preferably 40 to 70° C., and the mixing process is carried out under stirring conditions.

[0023] Furthermore, in the specific preparation process of the above-mentioned chemical precipitation method, the pH of the system can be adjusted by adding an alkaline solution, preferably by slow dripping. The alkaline solution can be an inorganic alkaline solution, specifically at least one of potassium hydroxide solution and ammonia water. Generally, the concentration of potassium hydroxide solution is 0.1-2 mol / L; the concentration of ammonia water is 15wt%-30wt%.

[0024] Furthermore, in the specific preparation process of the above chemical precipitation method, the aging treatment temperature is 15 to 60° C., and the treatment time is 2 to 10 hours.

[0025] Furthermore, in the specific preparation process of the above chemical precipitation method, separation can be carried out by any means that can achieve liquid-solid two-phase separation, such as filtration, centrifugal separation, etc.

[0026] Furthermore, in the specific preparation process of the above chemical precipitation method, during water washing, the weight ratio of water to solid product is 10:1 to 50:1, preferably 20:1 to 30:1.

[0027] Furthermore, in the specific preparation process of the chemical precipitation method, the drying temperature is 60-120° C., preferably 80-100° C., and the drying time is 2-24 hours, preferably 5-12 hours. The drying can be carried out by air drying or vacuum drying, preferably vacuum drying.

[0028] Furthermore, in the specific preparation process of the above chemical precipitation method, the binary composite precursor mainly includes a first gold hydroxide and a second metal hydroxide.

[0029] (ii) The specific preparation process of the redox precipitation method is as follows: the first metal precursor and the second metal precursor are mixed with water, and then an oxidant is introduced, and the pH of the solution is further adjusted to 7-9 to obtain a suspension, which is then aged, separated, washed with water, and dried to obtain a binary composite precursor.

[0030] Furthermore, in the specific preparation process of the above redox precipitation method, the first metal precursor is a salt containing the first metal, which can be an inorganic salt and / or an organic salt, specifically one or more of nitrate, sulfate, acetate, and chloride. Furthermore, the first metal precursor is one or more of manganese nitrate, manganese chloride, manganese sulfate, and manganese acetate.

[0031] Furthermore, in the specific preparation process of the above-mentioned redox precipitation method, the second metal precursor is a rare earth element compound, preferably a cerium or lanthanum compound, and can be specifically selected from one or more of cerium nitrate, cerium sulfate, cerium chloride, cerium acetate, lanthanum chloride, lanthanum nitrate, lanthanum sulfate, and lanthanum acetate.

[0032] Furthermore, in the specific preparation process of the redox precipitation method, the mixing temperature of the first metal precursor, the second metal precursor and water is 20 to 80° C., preferably 40 to 70° C., and the mixing process is carried out under stirring conditions.

[0033] Furthermore, in the specific preparation process of the above redox precipitation method, the weight ratio of the first metal precursor to the second metal precursor is 10:1 to 1:1, preferably 8:1 to 2:1.

[0034] Furthermore, in the specific preparation process of the above chemical precipitation method, the total molar concentration of the first metal precursor and the second metal precursor in the aqueous solution is 0.05 to 2.0 mol / L, preferably 0.05 to 1.5 mol / L.

[0035] Furthermore, in the specific preparation process of the redox precipitation method, the oxidant is one or more of potassium permanganate, potassium perchlorate, hydrogen peroxide, and nitric acid, preferably potassium permanganate. The mass ratio of the oxidant to the first metal precursor is 1:1 to 1:5, preferably 1:2 to 1:4.

[0036] Furthermore, in the specific preparation process of the above-mentioned redox precipitation method, the pH of the system can be adjusted by adding an alkaline solution, preferably by slow dripping. The alkaline solution can be an inorganic alkaline solution, specifically at least one of potassium hydroxide solution and ammonia water. Generally, the concentration of potassium hydroxide solution is 0.5-2 mol / L; the concentration of ammonia water is 15wt%-30wt%.

[0037] Furthermore, in the specific preparation process of the above redox precipitation method, the aging treatment temperature is 15 to 60° C. and the treatment time is 2 to 10 hours. Separation can be carried out by any means that can achieve liquid-solid two-phase separation, such as filtration, centrifugal separation, etc.

[0038] Furthermore, in the specific preparation process of the above redox precipitation method, during water washing, the weight ratio of water to solid product is 10:1 to 50:1, preferably 20:1 to 30:1.

[0039] Furthermore, in the specific preparation process of the redox precipitation method, the drying temperature is 60-120° C., preferably 80-100° C., and the drying time is 2-24 hours, preferably 5-12 hours. The drying can be carried out by forced air drying and vacuum drying, preferably vacuum drying.

[0040] Furthermore, in the specific preparation process of the above redox precipitation method, the binary composite precursor obtained by the redox precipitation method mainly includes the first metal oxide, the second metal hydroxide or a mixture of the first metal oxide, the first metal hydroxide and the second metal oxide.

[0041] Furthermore, in the above-mentioned preparation method of the activated carbon-containing composite material, the petroleum coke raw material in step (2) is a product obtained from the thermal processing process of the petroleum raw material, such as a solid product produced by a delayed coking device, and the particle size of the petroleum coke raw material is 10 to 500 μm, preferably 30 to 300 μm; the volatile matter content of the petroleum coke raw material is between 5wt% and 20wt%.

[0042] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the mass ratio of the petroleum coke raw material to the activating agent in step (2) is 1:0.2 to 1:10, preferably 1:0.5 to 1:5.

[0043] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the mass ratio of the first metal precursor to the petroleum coke raw material is 4:1 to 0.05:1, preferably 3:1 to 0.1:1.

[0044] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the gas in the activation device is fully replaced with an inert atmosphere before the activation treatment in step (3), and the inert atmosphere is one or more of nitrogen, helium, neon, argon, krypton, and xenon, preferably nitrogen and / or helium.

[0045] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the activation treatment temperature in step (3) is 700-1000° C., preferably 700-900° C.; the treatment time is 20-120 min, preferably 20-100 min.

[0046] Furthermore, in the above-mentioned preparation method of the composite material containing activated carbon, during the activation treatment process described in step (3), the thermal decomposition process of the binary composite precursor containing the first metal and the second metal is carried out simultaneously with the activation pore-forming process of the petroleum coke. During the process of the activator gradually forming and expanding the pores of the petroleum coke, the first metal oxide and the second metal oxide generated by the thermal decomposition of the binary composite precursor containing the first metal and the second metal participate in the reaction at the same time, and gradually disperse and deposit inside the pores as the pore-forming process proceeds. During the activation process of the petroleum coke, metal oxides with different valence states are generated in situ in the system, and there may also be a certain amount of metal elements. As the pores of the petroleum coke are enriched and developed, these metal oxides are evenly distributed on the inner and outer surfaces of the petroleum coke.

[0047] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the oxidation treatment temperature in step (4) is 20 to 200° C., preferably 20 to 150° C.; the oxidation treatment time is 20 to 240 min, preferably 30 to 180 min.

[0048] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the oxidizing atmosphere in step (4) is an oxygen-containing gas, which can be specifically selected from one or more of air, oxygen, and an oxygen-carrier gas mixture, preferably air and / or an oxygen-carrier gas mixture. Furthermore, the volume concentration of oxygen in the oxygen-carrier gas mixture is 2 to 30%, preferably 5 to 25%.

[0049] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the water washing in step (4) is washing with deionized water, distilled water or ultrapure water, and the liquid-to-solid mass ratio during water washing is 10:1 to 50:1, preferably 10:1 to 30:1.

[0050] Furthermore, in the above-mentioned method for preparing the activated carbon-containing composite material, the drying temperature in step (4) is 20 to 120° C., preferably 40 to 105° C.; and the drying time is 1 to 24 hours, preferably 4 to 12 hours.

[0051] Furthermore, in the preparation method of the above-mentioned activated carbon-containing composite material, in step (4), after the activation process of petroleum coke is completed, the valence state of the metal species on the surface of the activated carbon can be flexibly adjusted by an oxidation post-treatment method. During the activation of petroleum coke, the second metal oxide (cerium oxide / lanthanum oxide) is converted into an oxide with oxygen vacancies by contacting with high-temperature strongly reducing carbon, losing a considerable amount of oxygen from the lattice to form a large number of oxygen vacancies. When switched to an oxidizing atmosphere, the oxide with oxygen vacancies is easily re-oxidized to cerium oxide / lanthanum oxide when exposed to an oxidizing environment. In an oxidizing atmosphere, cerium oxide or lanthanum oxide can store and release oxygen through the mutual conversion of valence states, rapidly convert molecular oxygen in the oxidizing atmosphere into active oxygen, increase the concentration of active oxygen species through the generation and migration of oxygen vacancies, and accurately transfer the active oxygen species to the first metal of different valence states, thereby achieving selective low-temperature oxidation of the first metal and adjusting the amount of nano-first metal oxide on the surface of the activated carbon.

[0052] In order to achieve the above-mentioned purpose of the invention, the second aspect of the present invention provides an activated carbon-containing composite material obtained by the above-mentioned preparation method, wherein the composite material includes a first metal oxide, a second metal oxide and activated carbon. Based on the weight of the composite material, the content of the first metal oxide is 4 to 60%, preferably 5 to 50%; the content of the auxiliary metal oxide is 0.9 to 40%; preferably 1 to 30%; and the content of activated carbon is 20 to 95%, preferably 20 to 90%.

[0053] Furthermore, in the above-mentioned activated carbon-containing composite material, the activated carbon is petroleum coke-based activated carbon.

[0054] Furthermore, in the above activated carbon-containing composite material, the first metal is selected from one or more of Group VIIB and Group VIII metals, and specifically may be one or more of manganese, nickel, and cobalt, preferably manganese.

[0055] Furthermore, in the above activated carbon-containing composite material, the second metal is at least one of rare earth elements, preferably lanthanum and / or cerium.

[0056] Furthermore, in the above-mentioned activated carbon-containing composite material, the specific surface area of ​​the composite material is 300 to 2500 m 2 / g; preferably 500 to 1600 m 2 / g.

[0057] Furthermore, in the above-mentioned composite material containing activated carbon, the defect degree of the composite material is 0.8 to 2.0, preferably 0.9 to 1.7. The defect degree refers to the defect degree of the composite material at a wave number of 1590 cm in Raman analysis. -1 The absorption peak and wave number are at 1340 cm -1 The ratio of the peak intensities of the absorption peaks.

[0058] A third aspect of the present invention provides a working electrode, which comprises an activated carbon-containing composite material obtained by the above-mentioned preparation method.

[0059] The fourth aspect of the present invention provides a method for preparing a working electrode, comprising mixing an activated carbon composite material, a conductive agent, and a binder, coating the mixture on a current collector in the form of a slurry, pressing the mixture into an electrode sheet, and drying the sheet to obtain a working electrode.

[0060] Furthermore, in the above working electrode preparation method, the binder is one or more of polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), hydroxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF). Furthermore, in the above working electrode preparation method, the conductive agent is one or more of conductive carbon black, acetylene black, graphene, carbon nanotubes, conductive graphite, and carbon fiber.

[0061] Furthermore, in the above working electrode preparation method, the current collector is one or more of nickel foam, aluminum foil, titanium foil, copper foil, and carbon paper.

[0062] Furthermore, in the above working electrode preparation method, the usage ratio of the composite material, the conductive carbon black and the binder is 7-9:0.5-2:0.5-2.

[0063] Furthermore, in the above working electrode preparation method, the pressure of pressing the electrode sheet is 5 to 15 MPa.

[0064] Furthermore, in the above working electrode preparation method, the drying temperature of the electrode sheet is 40-100°C.

[0065] Compared with the prior art, the activated carbon-containing composite material and the preparation method thereof of the present invention have the following beneficial technical effects:

[0066] (1) In the composite material containing activated carbon of the present invention, not only can the metal oxide ensure the specific capacitance value of the composite material, but also the skeleton support of the carbon material can well alleviate the structural collapse of the metal oxide during the charge and discharge process, thereby ensuring the transfer of electrons. In addition, petroleum coke, which is widely available and inexpensive, is used as the raw material of the carbon material in the composite material, which has a significant advantage in raw material cost compared with carbon materials such as carbon aerogel, graphene, and carbon nanotubes.

[0067] (2) In the preparation method of the activated carbon-containing composite material of the present invention, petroleum coke-based activated carbon is used as a skeleton support, and the composite process of metal oxide and carbon material is carried out simultaneously with the activation process of petroleum coke, thereby achieving uniform dispersion of metal oxide on the inner and outer surfaces of the activated carbon, achieving structural stability of the active components of the composite material, and thereby increasing its long-term stability during electrochemical testing.

[0068] (3) The activated carbon-containing composite material prepared by the present invention fully utilizes the characteristics of large specific surface area of ​​petroleum coke-based activated carbon and layered graphite microcrystals that are conducive to electronic conduction. At the same time, the highly dispersed nanoscale first metal oxide can contribute to a higher specific capacitance value. At the same time, the high dispersion of the first metal oxide on the surface of the activated carbon is conducive to reducing the resistance value of the composite material, thereby solving the problem of high resistivity when the first metal oxide is used as an electrode material.

[0069] (4) In the preparation method of the activated carbon-containing composite material of the present invention, firstly, the molecular-level dispersion of the first metal and the second metal species is achieved through the preparation process of the binary composite precursor. The introduction of the second metal can not only prevent the accumulation of the first metal species during the activation process and play a better dispersion role, but also quickly convert the O2 in the oxidizing atmosphere into active oxygen during the post-oxidation treatment process, increase the concentration of active oxygen species through the generation and migration of oxygen vacancies, and selectively achieve low-temperature oxidation of the first metal, laying a foundation for the good electrochemical properties of the metal oxide-activated carbon composite material. DETAILED DESCRIPTION

[0070] The present invention will be further described below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0071] In the present invention, the specific surface area is obtained by nitrogen adsorption-desorption curve on Micromeritics ASAP 2020 adsorption instrument, the operating temperature is -196 ° C (liquid nitrogen temperature), the sample is pre-treated with dehydration at 300 ° C under nitrogen protection before testing, and the specific surface area is calculated by BET method. The degree of defect refers to the wave number at 1590 cm in Raman analysis. -1 The absorption peak and wave number are at 1340 cm -1 The ratio of the peak heights of the absorption peaks.

[0072] The properties of the petroleum coke raw material used in the present invention are as follows: sulfur content is 4.15wt%, volatile matter is 15.79wt%, and ash content is 0.79wt%.

[0073] Example 1

[0074] Weigh 2.4 g of manganese acetate (Mn(CH3COO)2▪4H2O) and 0.87 g of cerium nitrate (Ce(NO3)3▪6H2O) and add them to 50 mL of deionized water, stir until completely dissolved, place in a 70°C warm water bath and heat, adjust the pH to 8.0 with 30% ammonia water under stirring, continue stirring for 1 h, let stand for aging for 2 h, filter, wash with water, and dry the filter cake at 105°C for 4 h to obtain a manganese-based binary composite precursor.

[0075] Weigh 15.6g potassium hydroxide, mix and stir with manganese-based binary composite precursor and 5.2g petroleum coke powder, and put it into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 800℃ at 6℃ / min in a 500mL / min nitrogen atmosphere, and heat it at a constant temperature for 40min. Cool it down to 200℃ in a nitrogen atmosphere, switch the nitrogen to an oxygen-nitrogen mixed gas with an oxygen content of 5%, and after constant temperature oxidation treatment for 40min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 80℃ for 10h to obtain an activated carbon-manganese dioxide composite material. The composition of the composite material is 68.8wt% activated carbon, 22.0wt% manganese dioxide, and 9.2wt% cerium oxide; the specific surface area is 863m 2 / g; the degree of defect is 1.37.

[0076] Electrochemical performance test of composite materials:

[0077] The prepared activated carbon-manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60°C air drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1 mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 412F / g, and the specific capacitance retention rate after 2000 cycles is 94.8%.

[0078] Example 2

[0079] Weigh 0.63g of manganese acetate (Mn(CH3COO)2▪4H2O) and 2.17g of cerium nitrate (Ce(NO3)3▪6H2O) and add them to 30mL of deionized water, place in a 50℃ warm water bath and heat, and stir until completely dissolved. Weigh 1.47g of potassium permanganate (KMnO4) and dissolve in 50mL of water, slowly drop into the mixed solution under stirring, adjust the pH value of the mixed solution to 8.0 with 2mol / L KOH solution, stir for 30min, stop stirring, and place the suspension in a 50℃ water bath for aging for 2h, filter, wash with water, and dry the filter cake at 105℃ for 4h to obtain a manganese-based binary composite precursor.

[0080] Weigh 8.8g potassium hydroxide, mix and stir with manganese-based binary composite precursor and 4.4g petroleum coke powder, and put it into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 900℃ at 6℃ / min in a 500mL / min nitrogen atmosphere, and heat it at a constant temperature for 20min. Cool it down to 200℃ in a nitrogen atmosphere, switch the nitrogen to air with oxygen content, and after constant temperature oxidation treatment for 30min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 90℃ for 9h to obtain an activated carbon-manganese dioxide composite material. The composition of the composite material is 63.9wt% activated carbon, 11.1wt% manganese dioxide, and 25.0wt% cerium oxide; the specific surface area is 531m 2 / g; the degree of defect is 1.43.

[0081] Electrochemical performance test of composite materials:

[0082] The prepared activated carbon-manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, and placed in a 60℃ forced air drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the tablet, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 425F / g, and the specific capacitance retention rate after 2000 cycles is 92.6%.

[0083] Example 3

[0084] Weigh 3.16g of manganese nitrate (Mn(NO3)2▪4H2O) and 1.58g of cerium acetate (Ce(CH3COO)2▪nH2O) and add them to 300mL of deionized water, stir until completely dissolved, place in a 60℃ warm water bath for heating, adjust the pH to 8.5 with 1mol / L potassium hydroxide solution under stirring, continue stirring for 1h, let stand for aging for 2h, filter, wash with water, and dry the filter cake at 120℃ for 4h to obtain a manganese-based binary composite precursor.

[0085] Weigh 79.0g potassium hydroxide, mix and stir with manganese-based binary composite precursor and 31.6g petroleum coke powder, and put it into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 700℃ at 6℃ / min in a 500mL / min nitrogen atmosphere, and heat it at a constant temperature for 100min. Cool it down to 50℃ in a nitrogen atmosphere, switch the nitrogen to an oxygen-helium mixed gas with an oxygen content of 10%, and after constant temperature oxidation treatment for 180min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 100℃ for 7h to obtain an activated carbon-manganese dioxide composite material. The composition of the composite material is 89.0wt% activated carbon, 6.2wt% manganese dioxide, and 4.8wt% cerium oxide; the specific surface area is 1984m 2 / g; the degree of defect is 1.41.

[0086] Electrochemical performance test of composite materials:

[0087] The prepared activated carbon-manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, acetylene black and binder PTFE are mixed in a mass ratio of 7:2:1, then ground into a slurry and coated on the nickel foam, pressed into a sheet, and placed in a 60°C blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 368F / g, and the specific capacitance retention rate after 2000 cycles is 98.7%.

[0088] Example 4

[0089] Weigh 19.2 g of manganese acetate (Mn(CH3COO)2▪4H2O) and 2.4 g of lanthanum nitrate (La(NO3)2▪6H2O) and add them to 200 mL of deionized water, stir until completely dissolved, place in a 60°C warm water bath for heating, adjust the pH to 8.0 with 2 mol / L potassium hydroxide solution under stirring, continue stirring for 1 h, allow to stand for aging for 5 h, filter, wash with water, and dry the filter cake at 80°C for 6 h to obtain a manganese-based binary composite precursor.

[0090] Weigh 6.4g potassium hydroxide, mix and stir with manganese-based binary composite precursor and 6.4g petroleum coke powder, and put them into the activation furnace for heat treatment. First, replace the air in the activation furnace with 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 750℃ at 6℃ / min in 500mL / min nitrogen atmosphere, heat it at constant temperature for 100min, cool it down to 80℃ in nitrogen atmosphere, switch nitrogen to oxygen-nitrogen mixed gas with oxygen content of 15%, and after constant temperature oxidation treatment for 70min, switch to nitrogen atmosphere and cool it down to room temperature, then wash it with water and dry it at 105℃ for 8h to obtain activated carbon-manganese dioxide composite material. The composition of the composite material is 33.2wt% activated carbon, 58.9wt% manganese dioxide, and 7.9wt% lanthanum oxide; the specific surface area is 351m 2 / g; the degree of defect is 1.21.

[0091] Electrochemical performance test of composite materials:

[0092] The prepared activated carbon-manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, acetylene black and binder PTFE are mixed in a mass ratio of 7:1.5:1.5, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60°C blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1 mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 221F / g, and the specific capacitance retention rate after 2000 cycles is 68.4%.

[0093] Example 5

[0094] Weigh 2.3 g of cobalt nitrate (Co(NO3)2▪6H2O) and 0.6 g of cerium nitrate (Ce(NO3)3▪6H2O) and add them to 80 mL of deionized water, stir until completely dissolved, place in a 40°C warm water bath and heat, adjust the pH to 9.0 with 20 wt% ammonia solution under stirring, continue stirring for 1 h, let stand and age for 4 h, filter, wash with water, and dry the filter cake at 100°C for 6 h to obtain a cobalt-based binary composite precursor.

[0095] Weigh 53.0g potassium hydroxide, mix with cobalt-based binary composite precursor and 10.6g petroleum coke powder, stir and powder, and put into the activation furnace for heat treatment. First, replace the air in the activation furnace with 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 900℃ at 6℃ / min in 500mL / min nitrogen atmosphere, and heat it at constant temperature for 20min. Cool it down to 20℃ in nitrogen atmosphere, switch nitrogen to oxygen-nitrogen mixed gas with 5% oxygen content, and after constant temperature oxidation treatment for 120min, switch to nitrogen atmosphere and cool it down to room temperature, then wash it with water and dry it at 110℃ for 6h to obtain activated carbon-cobalt oxide composite material. The composition of the composite material is 86.4wt% activated carbon, 9.7wt% cobalt oxide, 3.9wt% cerium oxide; the specific surface area is 1563m 2 / g; the degree of defect is 1.16.

[0096] Electrochemical performance test of composite materials:

[0097] The prepared activated carbon-cobalt oxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, acetylene black and binder PVDF are mixed in a mass ratio of 7:1.5:1.5, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60℃ blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 2mol / L potassium hydroxide aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 281F / g, and the specific capacitance retention rate after 2000 cycles is 85.9%.

[0098] Example 6

[0099] Weigh 2.6 g of nickel nitrate (Ni (NO3)2▪6H2O) and 0.8 g of cerium nitrate (Ce(NO3)3▪6H2O) and add them to 130 mL of deionized water, stir until completely dissolved, place in a 60°C warm water bath and heat, adjust the pH to 9.0 with 20 wt% ammonia solution under stirring, continue stirring for 1 h, let stand and age for 4 h, filter, wash with water, and dry the filter cake at 100°C for 6 h to obtain a nickel-based binary composite precursor.

[0100] Weigh 44.8g potassium hydroxide, mix and stir with nickel-based binary composite precursor and 11.2g petroleum coke powder, and put it into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 800℃ at 6℃ / min in a 500mL / min nitrogen atmosphere, and heat it at a constant temperature for 70min. Cool it down to 30℃ in a nitrogen atmosphere, switch the nitrogen to an oxygen-nitrogen mixed gas with an oxygen content of 5%, and after constant temperature oxidation treatment for 150min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 120℃ for 5h to obtain an activated carbon-nickel oxide composite material. The composition of the composite material is 85.0wt% activated carbon, 10.2wt% nickel oxide, and 4.8wt% cerium oxide; the specific surface area is 1433m 2 / g; the degree of defect is 1.26.

[0101] Electrochemical performance test of composite materials:

[0102] The prepared activated carbon-cobalt oxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, acetylene black and binder PVDF are mixed in a mass ratio of 7:1.5:1.5, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60℃ blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 2mol / L potassium hydroxide aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 267F / g, and the specific capacitance retention rate after 2000 cycles is 86.2%.

[0103] Example 7

[0104] Weigh 2.08g manganese sulfate (MnSO4) and 1.21g cerium nitrate (Ce(NO3)3▪6H2O) and add them to 120mL deionized water, place in a 60℃ warm water bath and heat, stir until completely dissolved. Weigh 1.5g potassium permanganate (KMnO4) and dissolve in 50mL water, slowly drop into the mixed solution under stirring conditions, stir for 60min, adjust the pH value of the mixed solution to 9.5 with 1mol / L KOH solution, stir for 30min, stop stirring, and place the suspension in a 30℃ water bath for aging for 2h, filter, wash with water, and dry the filter cake at 105℃ for 4h to obtain a manganese-based binary composite precursor.

[0105] Weigh 25.2g potassium hydroxide, mix with manganese-based binary composite precursor and 12.2g petroleum coke powder, stir and powder, and put into the activation furnace for heat treatment. First, replace the air in the activation furnace with 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 850℃ at 6℃ / min in 500mL / min nitrogen atmosphere, and heat it at constant temperature for 50min. Cool it down to 150℃ in nitrogen atmosphere, switch nitrogen to oxygen-nitrogen mixed gas with oxygen content of 8%, and after constant temperature oxidation treatment for 70min, switch to nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 115℃ for 6h to obtain activated carbon-manganese dioxide composite material. The composition of the composite material is activated carbon 76.8wt%, manganese dioxide 17.2wt%, cerium oxide 6.0wt%; the specific surface area is 1506m 2 / g; the degree of defect is 1.36.

[0106] Electrochemical performance test of composite materials:

[0107] The prepared activated carbon-manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, graphene and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into a slurry and coated on the nickel foam, and placed in a 60℃ forced air drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the tablet, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 385F / g, and the specific capacitance retention rate after 2000 cycles is 86.2%.

[0108] Example 8

[0109] Weigh 12.9g of manganese chloride (MnCl2▪H2O) and 2.6g of cerium nitrate (Ce(NO3)3▪6H2O) and add them to 250mL of deionized water, place in a 60℃ warm water bath and heat, and stir until completely dissolved. Weigh 3.2g of potassium permanganate (KMnO4) and dissolve in 100mL of water, slowly drop into the mixed solution under stirring conditions, stir for 60min, adjust the pH value of the mixed solution to 9.5 with 1.5mol / L KOH solution, stir for 30min, stop stirring, and place the suspension in a 30℃ water bath for aging for 2h, filter, wash with water, and dry the filter cake at 120℃ for 6h to obtain a manganese-based binary composite precursor.

[0110] Weigh 46.8g potassium hydroxide, mix and stir with manganese-based binary composite precursor and 15.6g petroleum coke powder, and put it into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 850℃ at 6℃ / min in a 500mL / min nitrogen atmosphere, and heat it at a constant temperature for 50min. Cool it down to 100℃ in a nitrogen atmosphere, switch the nitrogen to an oxygen-nitrogen mixed gas with an oxygen content of 6%, and after constant temperature oxidation treatment for 120min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 90℃ for 8h to obtain an activated carbon-manganese dioxide composite material. The composition of the composite material is 58.9wt% activated carbon, 33.3wt% manganese dioxide, and 7.8wt% cerium oxide; the specific surface area is 703m 2 / g; the degree of defect is 1.45.

[0111] Electrochemical performance test of composite materials:

[0112] The prepared activated carbon-manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, carbon nanotubes and binder PVDF are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, and placed in a 60℃ forced air drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, pressed into a sheet, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 257F / g, and the specific capacitance retention rate after 2000 cycles is 81.7%.

[0113] Comparative Example 1

[0114] Weigh 3.6g petroleum coke and 10.8g potassium hydroxide, mix and stir to powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen flow at room temperature for 20min, then heat it to 850℃ at 6℃ / min in a 200mL / min nitrogen atmosphere, and heat treat it at a constant temperature for 50min. Then, the nitrogen atmosphere is lowered to room temperature to obtain a petroleum coke-based activated carbon material with a specific surface area of ​​2436m 2 / g; the degree of defect is 0.96.

[0115] The prepared petroleum coke-based activated carbon material is applied to supercapacitors. The preparation process of the working electrode is as follows: the petroleum coke-based activated carbon material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60°C blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 1 mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 268F / g, and the specific capacitance retention rate after 2000 cycles is 98.4%.

[0116] Comparative Example 2

[0117] Weigh 19.2g of manganese acetate (Mn(CH3COO)2▪4H2O) and 2.4g of lanthanum nitrate (La(NO3)2▪6H2O) and add them to 200mL of deionized water, stir until completely dissolved, place in a 60℃ warm water bath and heat, adjust the pH to 8.0 with 2mol / L potassium hydroxide solution under stirring, continue stirring for 1h, let stand for aging for 5h, filter, wash with water, and dry the filter cake at 80℃ for 6h to obtain a manganese-based binary composite precursor, which is then placed in an activation furnace for heat treatment. Treatment, first replace the air in the activation furnace with a 500mL / min nitrogen flow at room temperature for 20 minutes, heat up to 750°C at 6°C / min in a 500mL / min nitrogen atmosphere, heat treat at a constant temperature for 100 minutes, cool down to 80°C in a nitrogen atmosphere, switch nitrogen to an oxygen-nitrogen mixed gas with an oxygen content of 15%, and after constant temperature oxidation treatment for 70 minutes, switch to a nitrogen atmosphere and cool to room temperature, then wash with water and dry at 105°C for 6 hours to obtain a manganese dioxide material. The material composition is 88.2wt% manganese dioxide, 11.8wt% lanthanum oxide; the specific surface area is 86m 2 / g.

[0118] Electrochemical performance test of composite materials:

[0119] The prepared manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, acetylene black and binder PVDF are mixed in a mass ratio of 7:1.5:1.5, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60°C air drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 137F / g, and the specific capacitance retention rate after 2000 cycles is 53.1%.

[0120] Comparative Example 3

[0121] Weigh 12.9 g of manganese chloride (MnCl2▪H2O) and 2.6 g of cerium nitrate (Ce(NO3)3▪6H2O) and add them to 250 mL of deionized water. Heat in a 60°C warm water bath and stir until completely dissolved. Weigh 3.2g potassium permanganate (KMnO4) and dissolve it in 100mL water. Slowly add it dropwise to the mixed solution under stirring conditions and stir for 60min. Adjust the pH value of the mixed solution to 9.5 with 1.5mol / L KOH solution. After stirring for 30min, stop stirring. The suspension is aged in a 30℃ water bath for 2h, filtered, washed with water, and the filter cake is dried at 120℃ for 6h to obtain a manganese-based binary composite precursor, which is loaded into an activation furnace for heat treatment. First, the air in the activation furnace is replaced with a 500mL / min nitrogen flow at room temperature for 20min, and the temperature is increased to 850℃ at 6℃ / min under a 500mL / min nitrogen atmosphere. The material is heat treated at a constant temperature for 50min, cooled to 100℃ in a nitrogen atmosphere, and the nitrogen is switched to an oxygen-nitrogen mixed gas with an oxygen content of 6%. After constant temperature oxidation treatment for 120min, the material is switched to a nitrogen atmosphere and cooled to room temperature. The material is then washed with water and dried at 110℃ for 7h to obtain a manganese dioxide material. The material composition is 81.1wt% manganese dioxide and 18.9wt% cerium oxide; the specific surface area is 79m 2 / g.

[0122] Electrochemical performance test of composite materials:

[0123] The prepared manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, and placed in a 60℃ forced air drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the tablet, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 163F / g, and the specific capacitance retention rate after 2000 cycles is 56.2%.

Claims

1. A method for preparing a composite material containing activated carbon, comprising the following steps: (1) preparing a binary composite precursor containing a first metal and a second metal, wherein the first metal is selected from one or more of Group VIIB and Group VIII metals; and the second metal is at least one of rare earth elements; (2) mixing the binary composite precursor obtained in step (1), a petroleum coke raw material, and an activator to obtain a composite material precursor; (3) Under inert atmosphere conditions, the composite material precursor is activated to obtain an activated product; the activation treatment temperature is 700 to 1000° C.; the treatment time is 20 to 120 min; (4) Under oxidative atmosphere conditions, the activated product is oxidized, and then further washed and dried to obtain an activated carbon-containing composite material; the oxidation treatment temperature is 20 to 200° C.; the oxidation treatment time is 20 to 240 min.

2. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: The first metal is selected from one or more of manganese, nickel and cobalt.

3. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: The first metal is manganese.

4. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: The second metal is lanthanum and / or cerium.

5. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: In step (1), the binary composite precursor containing the first metal and the second metal is prepared by a chemical precipitation method or a redox precipitation method.

6. The method for preparing the composite material containing activated carbon according to claim 5, characterized in that: The preparation process of the chemical precipitation method is as follows: the first metal precursor and the second metal precursor are mixed with water, the pH value of the system is adjusted to 7.0-10.0, and then the binary composite precursor is obtained through aging, separation, water washing and drying.

7. The method for preparing the composite material containing activated carbon according to claim 6, characterized in that: The first metal precursor is a salt containing a first metal.

8. The method for preparing the composite material containing activated carbon according to claim 6 or 7, characterized in that: The first metal precursor is one or more of nitrate, sulfate, acetate and chloride.

9. The method for preparing the composite material containing activated carbon according to claim 6 or 7, characterized in that: The first metal precursor is one or more of manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, nickel nitrate, nickel chloride, nickel acetate, nickel sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, and cobalt sulfate.

10. The method for preparing the composite material containing activated carbon according to claim 6, characterized in that: The second metal precursor is a rare earth element compound.

11. The method for preparing the composite material containing activated carbon according to claim 6 or 10, characterized in that: The second metal precursor is a cerium or lanthanum compound.

12. The method for preparing the composite material containing activated carbon according to claim 6 or 10, characterized in that: The second metal precursor is selected from one or more of cerium nitrate, cerium sulfate, cerium chloride, cerium acetate, lanthanum chloride, lanthanum nitrate, lanthanum sulfate, and lanthanum acetate.

13. The method for preparing the composite material containing activated carbon according to claim 6, characterized in that: The weight ratio of the first metal precursor to the second metal precursor is 10:1 to 1:

1.

14. The method for preparing the composite material containing activated carbon according to claim 6, characterized in that: The weight ratio of the first metal precursor to the second metal precursor is 8:1 to 2:

1.

15. The method for preparing the composite material containing activated carbon according to claim 6, characterized in that: The pH of the system is adjusted by adding an alkaline solution, wherein the alkaline solution is an inorganic alkaline solution, and at least one of a potassium hydroxide solution and an ammonia solution is used.

16. The method for preparing the composite material containing activated carbon according to claim 6, characterized in that: The aging treatment temperature is 15-60°C and the treatment time is 2-10h.

17. The method for preparing the composite material containing activated carbon according to claim 6, characterized in that: The drying temperature is 60-120°C.

18. The method for preparing the composite material containing activated carbon according to claim 6 or 17, characterized in that: The drying temperature is 80-100°C.

19. The method for preparing the composite material containing activated carbon according to claim 5, characterized in that: The preparation process of the redox precipitation method is as follows: the first metal precursor and the second metal precursor are mixed with water, and then an oxidant is introduced, and the pH of the solution is further adjusted to 7-9 to obtain a suspension, which is then aged, separated, washed, and dried to obtain a binary composite precursor.

20. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The first metal precursor is a salt containing a first metal.

21. The method for preparing the composite material containing activated carbon according to claim 19 or 20, characterized in that: The first metal precursor is one or more of nitrate, sulfate, acetate and chloride.

22. The method for preparing the composite material containing activated carbon according to claim 19 or 20, characterized in that: The first metal precursor is one or more of manganese nitrate, manganese chloride, manganese sulfate and manganese acetate.

23. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The second metal precursor is a rare earth element compound.

24. The method for preparing the composite material containing activated carbon according to claim 19 or 23, characterized in that: The second metal precursor is a cerium or lanthanum compound.

25. The method for preparing the composite material containing activated carbon according to claim 19 or 23, characterized in that: The second metal precursor is selected from one or more of cerium nitrate, cerium sulfate, cerium chloride, cerium acetate, lanthanum chloride, lanthanum nitrate, lanthanum sulfate, and lanthanum acetate.

26. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The mixing temperature of the first metal precursor, the second metal precursor and water is 20-80° C., and the mixing process is carried out under stirring conditions.

27. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The mixing temperature of the first metal precursor, the second metal precursor and water is 40-70° C., and the mixing process is carried out under stirring conditions.

28. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The weight ratio of the first metal precursor to the second metal precursor is 10:1 to 1:

1.

29. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The weight ratio of the first metal precursor to the second metal precursor is 8:1 to 2:

1.

30. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The total molar concentration of the first metal precursor and the second metal precursor in the aqueous solution is 0.05-2.0 mol / L.

31. The method for preparing the composite material containing activated carbon according to claim 19 or 30, characterized in that: The total molar concentration of the first metal precursor and the second metal precursor in the aqueous solution is 0.05-1.5 mol / L.

32. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The oxidant is one or more of potassium permanganate, potassium perchlorate, hydrogen peroxide and nitric acid.

33. The method for preparing the composite material containing activated carbon according to claim 19 or 32, characterized in that: The oxidizing agent is potassium permanganate.

34. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The mass ratio of the oxidant to the first metal precursor is 1:1 to 1:

5.

35. The method for preparing the composite material containing activated carbon according to claim 19 or 34, characterized in that: The mass ratio of the oxidant to the first metal precursor is 1:2 to 1:

4.

36. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The pH of the system is adjusted by adding an alkaline solution, wherein the alkaline solution is an inorganic alkaline solution.

37. The method for preparing the composite material containing activated carbon according to claim 19 or 36, characterized in that: The pH of the system is adjusted by adding an alkaline solution in a slow dripping manner, wherein the alkaline solution is at least one of a potassium hydroxide solution and an ammonia solution.

38. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The aging treatment temperature is 15-60°C and the treatment time is 2-10h.

39. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The drying temperature is 60-120°C.

40. The method for preparing the composite material containing activated carbon according to claim 19, characterized in that: The drying temperature is 80-100°C.

41. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: In step (2), the mass ratio of the petroleum coke raw material to the activating agent is 1:0.2 to 1:

10.

42. The method for preparing the composite material containing activated carbon according to claim 1 or 41, characterized in that: In step (2), the mass ratio of the petroleum coke raw material to the activator is 1:0.5 to 1:

5.

43. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: In step (2), the mass ratio of the binary composite precursor to the petroleum coke raw material is 4:1 to 0.05:

1.

44. The method for preparing the composite material containing activated carbon according to claim 1 or 43, characterized in that: In step (2), the mass ratio of the binary composite precursor to the petroleum coke raw material is 3:1 to 0.1:

1.

45. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: In step (3), before the activation treatment, the gas in the activation device is fully replaced with an inert atmosphere, wherein the inert atmosphere is one or more of nitrogen, helium, neon, argon, krypton, and xenon.

46. ​​The method for preparing the composite material containing activated carbon according to claim 45, characterized in that: The inert atmosphere is nitrogen and / or helium.

47. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: In step (3), the activation treatment temperature is 700-900° C. and the treatment time is 20-100 min.

48. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: In step (4), the oxidation treatment temperature is 20 to 150° C. and the oxidation treatment time is 30 to 180 min.

49. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: The oxidizing atmosphere in step (4) is an oxygen-containing gas selected from one or more of air, oxygen, and an oxygen-carrier gas mixture, wherein the volume concentration of oxygen in the oxygen-carrier gas mixture is 2 to 30%.

50. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: The oxidizing atmosphere in step (4) is an oxygen-containing gas selected from air and / or an oxygen-carrier gas mixture, wherein the volume concentration of oxygen in the oxygen-carrier gas mixture is 5 to 25%.

51. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: The drying temperature in step (4) is 20 to 120°C.

52. The method for preparing the composite material containing activated carbon according to claim 1, characterized in that: The drying temperature in step (4) is 40 to 105°C.

53. An activated carbon-containing composite material obtained by the preparation method described in any one of claims 1 to 52.

54. The composite material containing activated carbon according to claim 53, characterized in that: The composite material comprises a first metal oxide, a second metal oxide and activated carbon. Based on the weight of the composite material, the content of the first metal oxide is 4-60%, the content of the auxiliary metal oxide is 0.9-40%, and the content of the activated carbon is 20-95%.

55. The composite material containing activated carbon according to claim 53, characterized in that: The composite material comprises a first metal oxide, a second metal oxide and activated carbon. Based on the weight of the composite material, the content of the first metal oxide is 5-50%, the content of the auxiliary metal oxide is 1-30%, and the content of the activated carbon is 20-90%.

56. The composite material containing activated carbon according to claim 54 or 55, characterized in that: The activated carbon is petroleum coke based activated carbon.

57. The composite material containing activated carbon according to claim 54 or 55, characterized in that: The first metal is selected from one or more of Group VIIB and Group VIII metals.

58. The composite material containing activated carbon according to claim 54 or 55, characterized in that: The first metal is selected from one or more of manganese, nickel and cobalt.

59. The composite material containing activated carbon according to claim 54 or 55, characterized in that: The first metal is manganese.

60. The composite material containing activated carbon according to claim 54 or 55, characterized in that: The second metal is at least one of rare earth elements.

61. The composite material containing activated carbon according to claim 54 or 55, characterized in that: The second metal is lanthanum and / or cerium.

62. The composite material containing activated carbon according to any one of claims 53 to 55, characterized in that: The specific surface area of ​​the composite material is 300 to 2500 m 2 / g.

63. The composite material containing activated carbon according to any one of claims 53 to 55, characterized in that: The specific surface area of ​​the composite material is 500~1600m 2 / g.

64. The composite material containing activated carbon according to any one of claims 53 to 55, characterized in that: The defect degree of the composite material is 0.8 to 2.0, and the defect degree refers to the defect degree of the composite material at the wave number of 1590 cm in Raman analysis. -1 The absorption peak and wave number are at 1340 cm -1 The ratio of the peak intensities of the absorption peaks.

65. The composite material containing activated carbon according to any one of claims 53 to 55, characterized in that: The defect degree of the composite material is 0.9 to 1.7, and the defect degree refers to the defect degree of the composite material at the wave number of 1590 cm in Raman analysis. -1 The absorption peak and wave number are at 1340 cm -1 The ratio of the peak intensities of the absorption peaks.

66. A working electrode, comprising the activated carbon-containing composite material as described in any one of claims 53 to 65.

Citation Information

Patent Citations

  • Preparation method of carbon particle / manganese dioxide composite electrode material

    CN105405680A

  • A carbon airgel / manganese dioxide composite electrode material with multi-level structure and its preparation method

    CN105826088B

  • Preparation method of carbon-manganese dioxide composite material

    CN108217733A

  • Preparation method of carbon nanotube / manganese dioxide composite electrode

    CN109637839A

  • Electrode material for lithium ion super-capacitor and preparation method thereof

    CN102832047A